Thermal fluctuations on the freeze-out surface of heavy-ion collisions and their impact on particle correlations - Aasen, Adrian Skasberg; Flörchinger, Stefan; Giacalone, Giuliano; Gündüz, Deniz (Physical review, 2023)
Particle momentum distributions originating from a quark-gluon plasma as produced in high-energy nuclear collisions can be influenced by thermal fluctuations in fluid dynamic fields. We study this effect by generalizing the commonly used kinetic freeze-out prescription by allowing for small fluctuations around an average in fluid velocity, chemical potentials, and temperature. This leads to the appearance of specific two-body momentum correlations. Combining a blast-wave parametrization of the kinetic freeze-out surface with the thermal correlation functions of an ideal resonance gas, we perform an exploratory study of angular net-charge correlations induced by thermal fluctuations around vanishing chemical potential. We note a diffusion of the near-side peak around Δy=Δϕ=0 induced by variances of different chemical potentials, which could be investigated experimentally.
Gesehen am 02.11.2023